The Effects of CAR (Choking Alert Response) Educational Video on Mothers' Knowledge and Skills in Responding to Choking in Toddlers - Abdullah Furqonudin; Meida Laely Ramdani (Proceedings Series on Health & Medical Sciences, 2026)
Background: Choking is an emergency condition caused by airway obstruction due to a foreign object and poses a serious risk to toddlers. Mothers’ knowledge and skills in managing choking incidents are essential to prevent severe complications. Health education using engaging educational videos can be an effective intervention, as video media enables rapid and memorable information delivery, helping mothers become more prepared and competent in handling choking situations. Method: This quantitative study employed a pre-experimental one-group pretest-posttest design. A total of 57 respondents were selected using non-probability incidental sampling. Instruments included a respondent characteristics questionnaire, a choking knowledge questionnaire, and a skills observation checklist. The intervention consisted of the CAR educational video, and data were analyzed using the Wilcoxon test. Results: The mean age of respondents was 27.75 years. Most participants were housewives (50.9%) and had junior high school education (36.8%). The mean knowledge score increased from 11.00 before the intervention to 19.00 after the intervention. The mean skills score improved from 9.00 to 15.00. Statistical analysis showed a significant effect of the CAR educational video on mothers’ knowledge and skills (p = 0.001). Conclusion: The CAR educational video effectively improved mothers’ knowledge and skills in managing choking incidents among toddlers.